2021
DOI: 10.1002/jmv.27521
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral intermediate uveitis in a healthy teenager with the multisystem inflammatory syndrome in children secondary to COVID‐19 infection

Abstract: To the Editor, Coronavirus disease 2019 (COVID-19) is a novel worldwide pandemic caused by the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). Children and adolescents generally present with mild symptoms. Nevertheless, 0.14% of them can develop a lifethreatening complication, the multisystem inflammatory syndrome in children (MIS-C). 1 This rare but serious condition can lead to multiorgan failure. To date, ocular reports associated with MIS-C are scarce. We report a case of bilateral intermedia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…Posterior involvement in KD is rare and is usually limited to case reports (13). Similarly, fundus findings in MIS-C are scarce in the literature, but some reports have demonstrated normal findings, as described in this case (6,7,9). Considering that both MIS-C and KD mainly involve the anterior segment of the eyes, we speculate that MIS-C and KD have a similar pathogenesis.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…Posterior involvement in KD is rare and is usually limited to case reports (13). Similarly, fundus findings in MIS-C are scarce in the literature, but some reports have demonstrated normal findings, as described in this case (6,7,9). Considering that both MIS-C and KD mainly involve the anterior segment of the eyes, we speculate that MIS-C and KD have a similar pathogenesis.…”
Section: Discussionmentioning
confidence: 75%
“…Therefore, MIS-C can present with various clinical features. While the literature is limited regarding ocular reports associated with MIS-C, anterior uveitis has recently been reported in addition to conjunctivitis (5)(6)(7)(8)(9). The present case was unique for the following two reasons: 1) the patient showed severe ocular manifestations as the primary symptom of MIS-C prior to other findings, such as fever or gastrointestinal manifestations, which could lead to delay in diagnosis, and 2) he suffered anterior scleritis, an unusual and severe form of inflammatory eye disease, rather than conjunctivitis.…”
Section: Discussionmentioning
confidence: 99%
“…A recent case report showed that a 14-year-old male pneumonia patient was diagnosed with COVID-19-associated bilateral anterior uveitis. The patient’s ocular symptoms improved after treatment with local and systemic corticosteroids [ 23 ]. Iriqat et al reported a case of anterior uveitis that occurred after recovery from COVID-19, which was severe but was relieved after local and systemic steroid treatment [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…22 Subsequently, several case reports have been reported. [23][24][25][26] Apart from case reports, in a study including the clinical features of 45 MISC patients from a single center, acute anterior uveitis was detected in 9 (20%) of 29 patients with ocular findings . 27 It has been stated in the publications that ocular findings improve with topical or systemic antiinflammatory therapy.…”
Section: Discussionmentioning
confidence: 99%
“…27 It has been stated in the publications that ocular findings improve with topical or systemic antiinflammatory therapy. [21][22][23][24][25][26][27] Apart from uveitis, cases of optic disc edema associated with MIS-C have been reported. 11,28 In our study, we did not find any signs of acute anterior uveitis or optic disc edema.…”
Section: Discussionmentioning
confidence: 99%